Surveys on the Security of Ethereum and Hyperledger Fabric Blockchain Platforms - Nik Mohd Kamal, Nik Nor Muhammad Saifudin; Afiqah, Safwah; Khadeja, Sara; Nasuha, Aliya; Wan Mohd Azman, Wan Muhammad Haziq Nur Iman; Wan Zulkifli, Wan Zul Irfan; Wan Anuar, Wan Shafiq Aiman; Isyraf Md Nazri, Muhammad Faizul; Zainuddin, Ahmad Anwar (International Journal on Perceptive and Cognitive Computing, 2025)
Ethereum and Hyperledger are two popular and well-known block chain platforms which represent two kinds of application differentiation. Ethereum is a decentralized platform that also allows DApps to operate on it; many of the conditions for performing functions on Ethereum’s blockchain do not require permission to be granted, but smart contracts are available. On the other hand, the Hyperledger Fabric, an enterprise grade blockchain solution, provides the permission to access, update, and apply scalability, privatization, and mandatory access control mechanisms. Due to the decentralized nature and the capacity of performing smart contracts using Ethereum Virtual Machine (EVM), it has been used in a number of areas across the world in financial transactions and DApp. Hyperledger fabric, on the other hand, is pursuant to the permissioned network standards and is centred on providing the set of components that suffice the requirement of an enterprise thereby making it easier for the organization to build a blockchain, which is both highly scalable and security conscious. Some of the studies have researched on Ethereum as well as Hyperledger Fabric in a variety of contexts as depicted by the following: From these studies, it explains how blockchain has the potential in increasing volume in various areas while enhancing its characteristics such as, openness, origin and audibility. Analysing the concrete features of the Ethereum and Hyperledger Fabric platforms, it is almost obligatory for the companies interested into the implementation of the blockchain technology to understand the possibilities offered by one system and the drawbacks some complexity or singularity of the other. That is why, the features of each platform are distinctive and could be utilized for the development of business processes in specific spheres when designing problem-solving approaches.